Validity of estimating active drag using the both assisted and resisted techniques with fluctuating velocity - Hazrati, P.; Mason, B.; Sinclair, P. J. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The main purpose of this study was to examine the validity of assisted and resisted techniques which are used for active drag estimation. Ten national and international male sprint swimmers performed two maximum effort free swims, two passive trials and two active drag trials in each technique. The computation of active drag for both techniques was based upon assumptions of the Velocity Perturbation Method (VPM) of Kolmogorov and Duplishcheva (1992). Results of a one-way ANOVA with repeated measures indicated there was no statistical significance between the active drag values obtained from the assisted and resisted techniques (p=0.05). There was however variation between active drag values. This is likely due to different power outputs that were applied during the test conditions and also, active drag varies as a function velocity squared.